Visografia : o problema do conteúdo, material e forma na escrita de sinais - Benassi, Claudio Alves (2019)
Sign writing is not a consensus among professionals in the sign language area. Its importance for the cognitive development of the visual subject (deaf) is still overlooked, and many of them do not even admit it as a possibility of effective register. VisoGrafia appears in this discredited scenario as a response to a need in the classroom while teaching sign writing in the Languages – Major in Sign Language) university course, where I work as a Professor. In my teachinglearning practice, I noticed that the best-known sign writing system, the Sign Writing (SW), is little viable for teaching because it contains 982 characters. The system I use, the Sign Language Writing (SLW) (Escrita das Línguas de Sinais) (ELiS), is rejected for being too abstract and, as a consequence, the VisoGrafia appears as an object of the present research, which aims mainly at creating a visual sign writing system, of easy memorization/mobilization in the spelling and reading process with a low number of graphemes. The system was developed in three phases: character selection; structuring and systematization; and application of the context of a teaching-learning situation. After the last phase, the system went through two improvement phases which enhanced the system and the spelling process, making it more visual. Currently, the system, which was created with 64 visographemes, now has only 37, being at present the spelling system with the fewest number of visographemes circulating in Brazil. Its main theoretical bases were the linguistic thoughts presented by Saussure and Bakhtin. From the former, his notion of system and from the latter, the idea of dialogue. The identified problem was analyzed, a process which indicated the need to guide the creation of the VisoGrafia by the assumptions of double articulation of language, proposed by Martinet. Thus, I described step by step the sign language in the first articulation level (morphemic) and in the second (paremological level). Such a use demands a new language concept, as well as a new structural linguistic concept of the sign language represented by the sequence: utterance; sign – morphic sign, distinctive sign; parameter; pareme; visual bundle. Thus, it was possible to understand and apply the double articulation principle of human language to sign language. Among the experiments carried out, I used the writing of three texts, being: a schedule, a note, and a poem. These proved the feasibility of the sign language spelling through signs of VisoGrafia, regardless of the writing genre. The reading feasibility was also experienced by reading the abstract of a scientific article in VisoGrafia, carried out by two Languages – Major in Sign Language students. Finally, it is worth highlighting that the VisoGrafia was applied to the teachinglearning process in an Extension course (offered to the community) and in extension subjects of sign writing in Languages – major in Sign Language courses. The students wrote and read signs in only two classes, and in eight they wrote texts, data that shows that VisoGrafia is an easy learning system.